Further extension of the generalized and improved (G′/G)-expansion method for nonlinear evolution equation - Naher, Hasibun; Abdullah, Farah Aini (© 2016 Elsevier B.V, 2016)
This article was published in the Journal of the Association of Arab Universities for Basic and Applied Sciences [© 2016 Published by Elsevier Inc.] and the definite version is available at: http://dx.doi.org/10.1016/j.jaubas.2014.05.005 The Journal's website is at: http://www.sciencedirect.com/science/article/pii/S1815385214000297